Many hands make light work: CNV of GSTM1 effect on the oral carcinoma risk. (June 2022) - Firigato, Isabela; López, Rossana V.M.; Curioni, Otávio A.; De Antonio, Juliana; Gattás, Gilka Fígaro; de Toledo Gonçalves, Fernanda
Abstract: Background: Genetic alterations of oral squamous cell carcinoma (OSCC) allow the understanding of the oral carcinogenesis and the identification of molecular biomarkers that aid the early diagnosis of the disease. The copy number variation (CNV) of GSTM1 and GSTT1 are promising targets because these two genes codify enzymes that perform the inactivation of tobacco carcinogens, which are the main risk factor of OSCC. However, the different levels of - detoxification mechanism in relation to each copy of the genes are unknown. Therefore, this study aimed to investigate the possible association of the CNV of GSTM1 and GSTT1 with the risk of development of OSCC. Methods: A total of 234 OSCC patients and 422 patients without any cancer diagnoses were recruited from Heliópolis Hospital from 2000 to 2011. The CNV was determined by TaqMan real-time PCR and the CopyCaller software. Odds ratio (OR) and 95% confidence interval (95% CI) values were calculated by Multiple Logistic Regression. Results: Most OSCC patients reported they continued smoking high amounts of cigarettes despite the tumor diagnosis. The CNV of GSTM1 varied from zero to two copies and the analysis revealed that two copies of GSTM1 decreased by 53% the OSCC risk (OR 0.47; 95% CI 0.24–0.92) and the risk of the tumor was modified according to the interaction of the CNV of GSTM1 and the cigarette smoking consumption, which for the amount of 40 packs-year of cigarettes the OSCC risk diminished progressively according to the increase of copies of GSTM1 . Although the GSTT1 gene varied from zero to three copies, none of them were associated with the tumor risk. Conclusion: The findings suggest that the CNV of GSTM1 might be applied as a tool for the surveillance of patients and the early detection of OSCC. Highlights: A novel methodology can distinguish the CNV of GSTM1 and GSTT1 . The differentially association of each copy of genes with the OSCC risk is unknown. The increased number of copies of GSTM1 seems to elevate the metabolism rate. Two copies of GSTM1 were associated with the decreased risk of OSCC. GSTM1 and GSTT1 enzymes are the mainly detoxifiers of cigarette smoking carcinogens.